Development And Evaluation Of An Antigen Detection Test For Hydatid Cyst Disease - Khanbabaie, Sam (2018)
Hydatid cyst disease (HCD) is a zoonotic parasitic disease which can infect both humans and animals. Imaging and antibody detection tests have been used to diagnose HCD, the former cannot differentiate between hydatid cyst and other pathologies; while the latter may not be able to differentiate between past and present infections, and may also not be suitable for evaluating treatment efficacy. In this regard, antigen detection tests may be able to assist in addressing the above issues. Previously it has been reported that hydatid cyst antigens can be detected in HCD patients using various assays.